Nazam Aceh in Translating the Qur'an: A Review of the Vernacularization of the Qur'an in Tafsir Pasé - Binti Yunus, Zulia Rahmi (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
This article aims to uncover the vernacularization activities of the Qur'an in the Aceh region. One of the efforts made by Indonesian scholars, including Acehnese scholars, in spreading Islamic teachings is the vernacularization (localization) of the meaning of the Qur'an so that its usefulness can be felt by all circles, as done by T. H. Thalhas et al. in the book of Tafsir Pasé. Through the descriptive-analytical method, it was found that Tafsir Pasé was the first interpretation to use the medium of nazam to interpret the meaning of the Qur'an in the Acehnese language. All the surahs on Juz 'Ammah and the letter Al-Fatihah are presented with the original text, Arabic, then accompanied by translations into Indonesian and Nazam Aceh. The vernacularization of verses of the Qur'an through Nazam Aceh on Tafsir Pasé focuses more on tarjamah tafsiriyyah, i.e., free translation, which is not too tied to the meaning of the original Arabic language. However, it refers to explaining the intention of words in Acehnese without limiting the original wording or consideration of language structure. Nazam Aceh dalam Menerjemahkan Al-Qur'an: Tinjauan Vernakularisasi Al-Qur'an dalam Tafsir Pasé. Artikel ini bertujuan untuk mengungkap aktivitas vernakularisasi al-Qur’an di wilayah Aceh. Salah satu usaha yang dilakukan oleh ulama-ulama Nusantara termasuk ulama Aceh dalam menyebarkan ajaran Islam yaitu melalui vernakularisasi (pem-bahasa-an lokal) makna al-Qur’an sehingga dapat dirasakan kemanfaatannya oleh semua kalangan, seperti yang dilakukan oleh Drs. T. H Thalhas dkk pada kitab Tafsir Pasé . Metode yang digunakan adalah deskriptif-analitik ditemukan bahwa, Tafsir Pasé merupakan tafsir pertama yang menggunakan media nazam untuk menafsirkan makna al-Qur’an ke dalam bahasa Aceh. Semua surah - surah pada Juz ‘Ammah beserta surat Al-Fatihah dipaparkan teks asli yaitu bahasa Arab, kemudian disertai penerjemahan Bahasa Indonesia dan juga nadzham Aceh.Vernakularisasi ayat-ayat al-Qur’an melalui nazam Aceh pada Tafsir Pasé lebih fokus kepada tarjamah tafsiriyyah yaitu terjemah bebas tidak terlalu terikat dengan makna bahasa aslinya bahasa Arab. Akan tetapi mengacu kepada penjelasan arti kata dalam Bahasa Aceh tanpa membatasi susunan kata-kata asli atau pertimbangan struktur bahasa.